European cooperation in developing earth building training standards: results of the PIRATE project - Keable, Rowland (2016)
Earth building in Europe has changed and developed over the past few decades. From a 1970’s non subject to an inspiring highly sustainable building form today many actions were needed across a group of countries. National earth building associations formed, initially discovering what could be achieved by working as a group within a national boundary. Through this, development began of national guidelines, codes and standards for earth building. One standards area was in training, because without training who will apply the guidelines, codes and standards on a building site? Who will have the knowledge, the skills and the competence? The interesting thing about this area was that it sought international co-operation. What is peculiar to training that looked for this co-operation? For whatever reasons the first project was conceived and began in 2001, 8 countries started develop training standards and a range of materials for earth plasters, what became the Learn•Clay project. After Learn•Clay the group had learned of the powerful body of knowledge and experience held in each national association. The next step was training standards for earth structures, a harder area to tackle due to it’s inherent perceived risks. A meeting was called using European mobilities funding (a system learned and understood through Learn•Clay). The initial meeting asked the basic question: is quantifying and codifying a training standard over a multi country area a good idea? Some of the partners were new to the discussion, others had developed their thinking more fully through the plasters project. Some had long experience in training and training structures while others had skills in earth building. This diversity of skills and experience subsequently became a powerful motor to the project. An application was made, 18 organisations from 8 countries mobilised to work together for 3 years in what became the PIRATE project. It was agreed the Units of Learning Outcomes should be for EQF levels 3-6, to capture the knowledge of already experienced workers, managers and designers. At the end of the project, after many hours and days of discussion, deliberation and testing a group of Units was added to the existing plaster units. As with plasters, the strength of working together was that a training standard in one country would be a step forward, a training standard simultaneously across 8 countries has a much broader reach. Before it was completed it had been taken up in the UK as a National Occupational Standard and this route to national certification is certainly a tool for dissemination available to all the other partners having worked on the Units. Working with standards beyond national boundaries within Regional Economic Communities (RECs) like the EU is extremely empowering. It may be used by other countries in the REC, and by other RECs. It may be a model for products and codes, harnessing the co-operation of the national groups and their knowledge and ability to work together. Certainly the experience of doing this work goes beyond the initial goals achieved in the project. By promoting the integration of ECVET learning outcomes into the national vocational training systems and by making the earth building “Learn.Earth” Training and Certification program more visible and available, new organizations around Europe are encouraged to join the network of partners. This is helping the earth family of professionals expand but it is also growing awareness around ECVET accreditation and sustainable building practices using earth throughout Europe.